How to report incidental findings from population whole-body MRI: view of participants of the German National Cohort - Hegedűs, Péter; Stackelberg, Oyunbileg von; Bertheau, Robert; Kauczor, Hans-Ulrich; Schlett, Christopher L.; Weckbach, Sabine (European radiology, 2019)
ObjectivesIn the German National Cohort (GNC), 30,000 individuals are examined with whole-body MRI (wbMRI), of which about 3000 participants are expected to receive an incidental finding (IF) disclosure. In order to get feedback from participants and to evaluate the IF-management procedure of the wbMRI substudy, a follow-up questionnaire was developed. This single-center pilot trial was aimed to get a first impression on feasibility reproducibility and validity of such a survey in order to take necessary adjustments before initiating the survey among several thousand participants.MethodsThe questionnaires were sent out in test-retest manner to 86 participants who received a wbMRI examination in January-February 2016 at the imaging center in Neubrandenburg. The ratio of participants with and without IF notification was 1:1. Descriptive statistics was performed.ResultsA first response of 94% and completion proportion of 99% were achieved. Participants were satisfied with the examination procedure. Ninety-five percent of participants considered it very important to receive notification of IFs. Participants reported minimal stress levels while waiting for a possible IF notification letter, but high stress levels when an IF letter was received. Phrasing of the IF reports was rated in 97% as well understandable and in 55% as beneficial to health status.ConclusionsThis questionnaire will serve researchers within the GNC as a fundamental instrument not only for quality management analyses but also for the investigation of still unacknowledged scientific and ethical questions contributing to evidence-based guidelines concerning the complex approach to IFs in future population-based imaging.Key Points • Evidence-based guidelines for reporting incidental findings in population whole-body MRI are lacking. • Pilot-testing of a questionnaire for the evaluation of practical and ethical aspects of the procedure to report incidental findings in the German National Cohort shows a high level of acceptance and high return rate by participants. • Participants reported minimal stress levels while waiting for a possible incidental finding notification letter, which increased significantly, when such a letter was received.
Gesehen am 11.11.2019